2019
DOI: 10.15171/hpp.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute exercise on episodic memory function among young university students: moderation considerations by biological sex

Abstract: Background: The objective of this study was to evaluate potential sex-specific differences on episodic memory function and determine whether sex moderates the effects of acute exercise on episodic memory.Methods: A randomized controlled intervention was employed. This experiment was conducted among young University students (mean age = 21 years). Both males (n=20) and females (n=20)completed two counterbalanced laboratory visits, with one visit involving a 15-minute bout of moderate-intensity exercise prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…Women showed better recognition memory than men, but there was improved object location memory only among men, and only among men who completed the memory task second. Another study did not note either an improvement in memory or sex moderation in improvement with a brief bout of moderate intensity exercise [32]. Lastly, an intervention study assessing the efficacy of a 6-month aerobic training in mitigating white matter hyperintensity progression in older adults with vascular cognitive impairment found that men who had completed the aerobic training intervention, in comparison to the women completing the same intervention, had significantly less white matter hyperintensity progression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Women showed better recognition memory than men, but there was improved object location memory only among men, and only among men who completed the memory task second. Another study did not note either an improvement in memory or sex moderation in improvement with a brief bout of moderate intensity exercise [32]. Lastly, an intervention study assessing the efficacy of a 6-month aerobic training in mitigating white matter hyperintensity progression in older adults with vascular cognitive impairment found that men who had completed the aerobic training intervention, in comparison to the women completing the same intervention, had significantly less white matter hyperintensity progression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, two meta-analyses conducted in 2003 and 2017 concluded that studies that included more women tended to show greater cognitive benefits associated with PA than studies with fewer women (Colcombe and Kramer, 2003;Barha et al, 2017). A randomized, controlled clinical trial evaluating the effect of acute PA on memory found that young women performed episodic memory tasks better than men (Johnson and Loprinzi, 2019). In addition to memory, studies evaluating the effect of endurance PA showed in elderly women a clear benefit on executive functions (Liu-Ambrose et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there was a greater proportion of females in our control group, which could have contributed to our null exercise interference findings. As we have demonstrated elsewhere [43], females tend to outperform males on verbal memory tasks; however, as we recently demonstrated [44], gender does not appear to moderate the effects of acute exercise on memory function.…”
Section: Discussionmentioning
confidence: 45%